Effectiveness of Modular Distance Learning in Tagaytay Kindergarten Schools During the Covid-19 Pandemic - Gatdula, Faith S. (2022)
Due to the COVID-19 outbreak, students and instructors have been unable to engage in face-to-face learning within the school. As a result of the epidemic, Modular Distance Learning has been implemented as an immediate reaction to maintain educational continuity. The Philippines is currently transitioning to a new normal type of education, and educators' constant innovations and active participation from other stakeholders are the driving forces behind its success. The main goal of this study was to learn about the obstacles, views, and recommendations of teachers, parents, and students who participated in the implementation of Modular Distance Learning at Tagaytay DepEd Elementary during the School Year 2020-2021. A mixed quantitative and qualitative approach was used to identify these difficulties, viewpoints, and recommendations. In the Philippines, striving to push through education despite the fatal pandemic caused by covid-19 has proven to be a difficult undertaking. The Commission on Higher Education (CHED) and the Department of Education (DepEd) Despite several objections, the California Department of Education (CHED)accepted and implemented the flexible blended learning strategy despite the risk of open classes due to the virus. Modular (Printed), Modular (Digital), Online, Educational TV, Radio-Based Instruction, Home Schooling, and Blended Learning is the many learning modalities. Online learning is implemented especially for high schools and colleges in cities Where modern living is adopted and students and learners have the privilege of having an internet connection at home, but it is also implemented for those living in rural areas or provinces where internet connection is not available. The new normal education, along with its many modalities, was first met with opposition due to the risk, but thanks to the efforts of education sectors in the Philippines, it is now being implemented systematically with the objective of continuing education despite the pandemic. The IATF, or Inter-Agency Task Force, is implementing several safety measures in order to avoid and reduce the spread of Covid-19 while the teaching and learning process continues in the country in order to preserve the health and welfare of teachers, parents, and pupils. Some of the safety procedures include adequate cleanliness of schools where modular learning is employed, as well as having alcohol stands in every classroom for parents' convenience. Teachers and parents must wear face masks and face shields while in the classroom, and social separation is severely enforced. They are advised to make thorough preparation for online learning and other modalities where parents and their children, as well as teachers, stay at home. Keywords: Modular Distance Learning, Home Schooling, Home Facilitators, Learning Modalities
Master Thesis